Kelor (Moringa oleifera) Bioactive Compounds as Potential Anti-Breast Cancer Agents: In Silico Studies - Saeful Amin; Vanessa Angelica Sheryl; Ade Yeni Aprillia; Anisa Pebiansyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Breast cancer is the most common type of cancer in women. Kelor (Moringa oleifera) leaves are a plant with medicinal properties for treatment. This study aimed to determine the activity and identify the metabolite compounds of M. oleifera leaves that are more effective and stable at the estrogen receptor (ER), potentially serving as an anticancer agent for breast cancer. The methods employed are computational studies, including molecular docking, PKCSM tests, and molecular dynamics simulations. The results of a computational molecular docking study of 23 M. oleifera leaf compounds identified the three best compounds from the docking results of the best ER genistein compounds on the 1QKM receptor, as well as genistein and luteolin compounds on the 1X7J receptor, all with low free energy values. From the pkCSM test of 23 compounds, three compounds were selected that showed good absorbance and distribution, and the toxicity prediction indicated that one compound did not exhibit hepatotoxicity. Molecular dynamics results for the Luteolin 1X7J compound, simulated for 100 ns, showed lower and more stable RMSD and RMSF values compared to those of compounds on the ER.